Les nouvelles perspectives frontalières de l’union européenne après l’élargissement de 2004 - André-Louis Sanguin (L'Espace Politique)
The concept and the practice of cross-border cooperation have their roots in the historical core of the present European Union, namely within the six founding States of the European Coal and Steel Community (1952). The ideas of Jean Monnet and Robert Schuman, two of the most famous founding fathers of the European integration, can be summarized according to the following assumption : by its involved multidimensional activities, the cross-border cooperation prevents potential conflicts between some former enemy countries (for instance, France and Germany). Obviously it is acting as a matter of integrative policy. Such a cross-border cooperation is an indirect step towards European unification because it is filling the vacuum which was left by the collapse of former unions like Comecon or the Warsaw Pact. It is necessary to stress that the cross-border cooperation takes its place upon hierarchical horizons in which the Euroregions constitute the most important stage. After the 2004 enlargement, which extended the European Union from 15 to 25 States, some real facts or new tendencies regarding the border issues are observable within and around the political scene of the new EU. The aim of this paper is to scrutinize these new outlooks.